2017
DOI: 10.3389/fimmu.2017.01818
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells in HIV/SIV Infections

Abstract: Over the past several years, new populations of innate lymphocytes have been described in mice and primates that are critical for mucosal homeostasis, microbial regulation, and immune defense. Generally conserved from mice to humans, innate lymphoid cells (ILC) have been divided primarily into three subpopulations based on phenotypic and functional repertoires: ILC1 bear similarities to natural killer cells; ILC2 have overlapping functions with TH2 cells; and ILC3 that share many functions with TH17/TH22 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 113 publications
(136 reference statements)
1
16
0
Order By: Relevance
“…While samples were negatively gated for CD127 to exclude innate lymphoid cells, [20] inclusion of CD127 expression on NKB did not alter the immunological profile.…”
Section: Methodsmentioning
confidence: 99%
“…While samples were negatively gated for CD127 to exclude innate lymphoid cells, [20] inclusion of CD127 expression on NKB did not alter the immunological profile.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, ILC3 depletion in HIV/SIV infection does not appear to be due to direct viral infection [ 130 , 136 ]. Rather, mechanistic studies have suggested that ILC3 depletion is the result of apoptosis, possibly due to dysregulation of ILC survival signals [ 137 ]. As such, analysis of ILC3 from humans with HIV-1 viremia shows upregulation of genes linked to apoptosis and cell death, including CD95 (Fas) [ 130 ].…”
Section: Loss Of Tolerance: Dysregulated Ilc3 Responses In Human Disementioning
confidence: 99%
“…Specific immunological abnormalities within the GI tract are known to contribute directly to progressive HIV/SIV infections. T regulatory (T reg ) CD4 ϩ cells, Th17 cells, Tc17 cells, and innate lymphocyte type III (ILC3) cells are preferentially and persistently lost from the lamina propria of the GI tract in people living with HIV and in SIV-infected macaques and are not restored with the administration of ARVs (54)(55)(56). The loss of these cells and altered infiltration of neutrophils into GI tract tissues (57) contribute to epithelial barrier defects, microbial translocation, and inflammation.…”
Section: Discussionmentioning
confidence: 99%